Species diversity and plastid DNA haplotype distributions of Pinus subsection Australes (Pinaceae) in Guerrero and Oaxaca - Ortiz-Martínez, Alfredo; Gernandt, David S. (TIP Revista Especializada en Ciencias Químico-Biológicas, 2016)
Pinus subsection Australes is a group of North American hard pines comprising approximately 29 ecologically and economically important tree species distributed throughout North and Central America and the Caribbean Islands. Previous studies have shown that some species of this subsection share plastid DNA haplotypes, a pattern that is attributed to introgressive hybridization or the retention of ancestral polymorphisms. Here we describe the morphological and plastid haplotype diversity for this group of species in the states of Guerrero and Oaxaca, Mexico. Seven species of Pinus subsection Australes are recognized in the study area, one of which, P. patula, includes two varieties. Seven variable sites and nine haplotypes were found in an 840 b.p. fragment of the DNA coding region ycf1. Shared haplotypes were found for P. patula var. patula, P. patula var. longipedunculata, P. herrerae, and P. tecunumanii. Four of the nine haplotypes found were restricted to Oaxaca. Although plastid DNA genealogies are valuable for studying evolution in this group, greater sampling of individuals and the inclusion of more variable sites are needed to more accurately infer species relationships.